CELALÜDDİN HIZIR (HACI PAŞA) MÜNTAHAB-I ŞİFA - İNCELEME-METİN-DİZİNLER - ÖNLER, ZAFER (Fırat Üniveristesi, 1981)
[Abstract Not Available]
Keywords: Halk Bilimi (Folklor); Folklore; Türk Dili ve Edebiyatı; Turkish Language and Literature